Post Marketing Surveillance on Propranolol and Atenolol Tablets Manufactured in Iran: Title: PMS of propranolol and atenolol tablets - Soghra Khabnadideh,; Soliman Mohammadi Samani,; Zahra Rezaei,; Gholamreza Yarmohammadi, (Iranian Journal of Pharmaceutical Sciences, 2010)
Propranolol, a prototypical b-adrenergic receptor antagonist and atenolol, a cardio-selective b-antagonist are widely used in therapeutic regimens for treatment of hypertensive patients. In Iran, several pharmaceutical manufacturers formulate these two b-blockers. As the formulation of a dosage form is essential for the patient's safety and drug efficacy, in this study we aimed to evaluate the quality of the tablets which are formulated by the above manufacturers. Atenolol (100 mg) tablet manufactured by APOTEX in Canada also was evaluated. The commercially available preparations of the following dosage forms were studied: propranolol (10 mg, 40 mg) manufactured by TOLID DARU and ROSE DARU (a, b, c, d), atenolol (50 mg) manufactured by DARUPAKHSH (e), atenolol (100 mg) manufactured by DARUPAKHSH, TOLID DARU, SOBHAN, LORESTAN and APOTEX (f, g, h,i, j). The quality and safety of the dosage forms of these drugs were evaluated by PMS studies. For this purpose, the weight variation, hardness, thickness, content assay, content uniformity, disintegration time and dissolution rate of the dosage forms were compared to British Pharmacopeia (BP) and United States Pharmacopeia (USP) standards. The results verify that all dosage forms show evidence of the USP and BP quality assessment.